The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1128/iai.74.1.390-393.2006
|View full text |Cite
|
Sign up to set email alerts
|

Complement and Fc Function Are Required for Optimal Antibody Prophylaxis againstPneumocystis cariniiPneumonia

Abstract: Pneumocystis carinii is an opportunistic fungal pathogen that causes P. carinii pneumonia (PCP) in the immunocompromised host. We investigated the role of antibody Fc-mediated function in passive prophylaxis against the development of PCP in SCID mice. By comparison of anti-mouse P. carinii immunoglobulin G1 monoclonal antibody (MAb) 4F11(G1) and its F(ab)2 derivative in an intranasal immunoprophylaxis model, we determined that Fc-mediated function is required for maximum effect of this antibody. Comparison of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…In recent years additional mechanisms of antibody action against fungi have been revealed, including growth inhibition (42), inhibition of biofilm formation (22), inhibition of adherence (24), inhibition of germination (24), and direct antifungal effects (24). For antibodies to C. albicans mannoproteins, Pneumocystis carinii surface antigen, and C. neoformans glucuronoxylomannan, the Fc region and/or complement was essential for antibody efficacy (15,41,44), whereas the activity of antibodies to other C. albicans mannoproteins (MP65) and heat shock protein 90 (9, 29) is mediated by antibody fragments (Fabs) and does not require Fc regions. Notably, antibodies to C. albicans MP65 and secretory aspartyl proteinase-2 that lack Fc regions were shown to inhibit fungal adherence to epithelial cells (9).…”
Section: Mechanisms Of Antibody-mediated Protectionmentioning
confidence: 99%
“…In recent years additional mechanisms of antibody action against fungi have been revealed, including growth inhibition (42), inhibition of biofilm formation (22), inhibition of adherence (24), inhibition of germination (24), and direct antifungal effects (24). For antibodies to C. albicans mannoproteins, Pneumocystis carinii surface antigen, and C. neoformans glucuronoxylomannan, the Fc region and/or complement was essential for antibody efficacy (15,41,44), whereas the activity of antibodies to other C. albicans mannoproteins (MP65) and heat shock protein 90 (9, 29) is mediated by antibody fragments (Fabs) and does not require Fc regions. Notably, antibodies to C. albicans MP65 and secretory aspartyl proteinase-2 that lack Fc regions were shown to inhibit fungal adherence to epithelial cells (9).…”
Section: Mechanisms Of Antibody-mediated Protectionmentioning
confidence: 99%
“…We have previously shown that administration of a Pca1-binding MAb (4F11) reduces organism burden, and maximal reduction of Pneumocystis after MAb infusion requires an intact Fc region and a functional complement system (29). Persistence of protection well after immunization and in the absence of CD4 ϩ T cells also is most consistent with antibody-mediated protection.…”
Section: Discussionmentioning
confidence: 71%
“…Antibody responses to surface proteins have been associated with protection from Pneumocystis pneumonia using both active and passive immunization approaches (1)(2)(3)(4)(5). These data suggest that antibody responses raised against surface epitopes can provide protection against Pneumocystis pneumonia potentially by enhancing opsonic phagocytosis or through activation of complement (6,7). A limitation of antigen discovery is the fact that Pneumocystis cannot be cultured in vitro.…”
mentioning
confidence: 99%